Selbstreparaturen in der schriftlichen Interaktion - Mostovaia, Irina (De Gruyter, 2022)
This empirical study examines self-initiated and other-initiated self-repairs in German and Russian SMS communication by applying methods from conversation analysis and interactional linguistics. It describes the sequential organization and functions of self-repairs in the analyzed data from the two languages and contrasts them with each other.